Incident Heart Failure in Atherosclerotic Renal Artery Stenosis: A Post Hoc Analysis of the CORAL Trial - Rajesh Gupta; Michelle M. Estrella; Rebecca Scherzer; Pamela S. Brewster; Lance D. Dworkin; Hanh T. Nguyen; Yanmei Xie; Joachim H. Ix; Michael G. Shlipak; Timothy P. Murphy; Donald E. Cutlip; Eldrin F. Lewis; et al. (Kidney Medicine)
Rationale & Objective: Although renal artery stenosis (RAS) and heart failure (HF) have been linked, the incidence and predictors of HF among patients with RAS are not well described. Study Design: Post hoc analysis of the Cardiovascular Outcomes in Renal Atherosclerotic Lesions (CORAL) multicenter, open-label, randomized controlled trial (RCT). Settings and Participants: Patients with atherosclerotic RAS and elevated blood pressure, chronic kidney disease, or both, and without a history of HF at enrollment. Intervention: Medical therapy alone versus medical therapy plus renal artery stenting. Outcomes: Incident HF events. Results: This analysis included 808 participants enrolled in the CORAL trial without evidence of baseline HF. During a median follow-up of 4.8 years, 54 participants (6.7%) developed incident HF. HF incidence rates did not differ by randomized intervention (HR, 0.84; 95% confidence interval [CI], 0.49-1.43 for stent arm with medical arm as reference). Baseline diabetes (subdistribution hazard ratio (sHR), 2.07; 95% CI, 1.20-3.58), albuminuria (sHR, 1.12 per doubling of urinary albumin-creatinine ratio, 95% CI, 1.02-1.24), lower eGFR (sHR, 0.78 per 10 mL/min/1.73 m2 estimated glomerular filtration rate calculated with cystatin C and creatinine, 95% CI, 0.69-0.88), and peripheral vascular disease (PVD) (sHR, 2.18, 95% CI, 1.21-3.91) were independent predictors of incident HF. Participants who experienced incident HF had greater kidney function decline before HF events. Limitations: This is a post hoc analysis of a RCT. The number of HF events is small. Conclusions: In patients with RAS, rates of incident HF did not differ between participants randomized to optimal medical therapy alone versus optimal medical therapy plus renal artery stenting. The presence of diabetes, PVD, and worse kidney health at baseline were associated with future HF events. Plain-Language Summary: Renal artery stenosis has been linked with heart failure. The CORAL randomized controlled trial has the largest study population of participants with renal artery stenosis. In this analysis, we assessed the incidence and predictors of heart failure in CORAL. We found similar rates of incident heart failure among participants randomized to medical therapy alone vs. medical therapy plus renal artery stent. We identified independent predictors of incident heart failure among people with renal artery stenosis include PAD, diabetes, albuminuria, and lower baseline eGFR. In addition, eGFR declined prior to heart failure events.